2023
DOI: 10.3390/plants12020330
|View full text |Cite
|
Sign up to set email alerts
|

ATANN3 Is Involved in Extracellular ATP-Regulated Auxin Distribution in Arabidopsis thaliana Seedlings

Abstract: Extracellular ATP (eATP) plays multiple roles in plant growth and development, and stress responses. It has been revealed that eATP suppresses growth and alters the growth orientation of the root and hypocotyl of Arabidopsis thaliana by affecting auxin transport and localization in these organs. However, the mechanism of the eATP-stimulated auxin distribution remains elusive. Annexins are involved in multiple aspects of plant cellular metabolism, while their role in response to apoplastic signals remains uncle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…Extracellular ATP (eATP) has been shown to play multiple roles in plant growth and development, including root growth and stress responses [6,18,20,40,41]. It has been reported that eATP suppresses growth and alters the growth orientation of the root and hypocotyl of Arabidopsis by affecting hormone signaling pathways [6,[41][42][43][44]. Some reports suggest that the P2K1 receptor is partially involved in eATP-mediated plant growth [44].…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular ATP (eATP) has been shown to play multiple roles in plant growth and development, including root growth and stress responses [6,18,20,40,41]. It has been reported that eATP suppresses growth and alters the growth orientation of the root and hypocotyl of Arabidopsis by affecting hormone signaling pathways [6,[41][42][43][44]. Some reports suggest that the P2K1 receptor is partially involved in eATP-mediated plant growth [44].…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence suggests that important secondary messengers, Ca 2+ and reactive oxygen species (ROS), mediate the signaling events following eATP perception by P2K1 (Choi et al., 2014; Demidchik et al., 2009; Gilroy et al., 2016; Jeter et al., 2004; Marcec et al., 2019; Tanaka et al., 2010; Tripathi et al., 2018). Additionally, eATP has been found to play a role in regulating plant growth and development, although the involvement of P2K1 in these processes has not been fully understood (Tang et al., 2003; Tonón et al., 2010; Xu et al., 2023; Zhu et al., 2020). Recent research has identified eATP‐responsive genes through transcriptomics (Jewell et al., 2019), leading to the development of a reliable tool for monitoring eATP signaling responses (Sowders & Tanaka, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In general, the C-terminal core of annexin contains four annexin repeats, and each repeat has five short α-helices [9,10]. Previous studies have shown that annexins participate in regulating diverse aspects of plant growth and development as well as responses to stress [11,12]. For example, the overexpression of TdANN6 enhanced salt/osmotic stress tolerance by increasing catalase (CAT), superoxide dismutase (SOD) and peroxidase (POD) activities in durum wheat [13].…”
Section: Introductionmentioning
confidence: 99%